Association of pSTAT3, pSyk with c-Myc, p53, BCL2 proteins expression and survival of patients with diffuse large B-cell lymphoma - V. A. Rosin; E. V. Vaneeva; D. A. Dyakonov; S. V. Samarina; I. V. Paramonov (Онкогематология)
Background. Diffuse large B cell lymphoma (DLBCL) is one of the most common non-Hodgkin’s lymphomas. The effectiveness of R-CHOP (rituximab, cyclophosphamide, hydroxydaunorubicin, oncovin, prednisone) therapy was observed in about 60 % of patients, in 20–30 % of cases DLBCL is characterized by a refractory course. Standard clinical prognostic criteria do not accurately determine the prognosis of the disease. In this regard, the problem of developing additional predictors of DLBCL course remains relevant today and is directly related to the molecular pathogenesis of the disease.The objective: to determine the relationship of pSTAT3, pSyk with c-Myc, p53, BCL2 oncoproteins expression and survival of DLBCL patients.Materials and methods. Biopsy specimens of lymph nodes and other organs and tissues obtained from 100 patients with newly diagnosed DLBCL were used for the study. All patients received standard first-line immunochemotherapy according to the R-CHOP regimen. Determination of the relative amount of tumor cells expressing pSTAT3, pSyk was carried out using immunohistochemical and morphometric methods. The threshold value of proteins expression was calculated using the ROC analysis: for pSTAT3 it was 68 % of positive tumor cells, for pSyk – 28 %. The relationship of pSTAT3, pSyk with c-Myc, p53, BCL2 expression was determined using the Pearson χ2  test. Overall (OS) and progression-free (PFS) survival were calculated using the Kaplan–Meier method (log-rank test).Results. The suprathreshold pSTAT3 expression was found to be associated with a high content of c-Myc and p53 transcription factors in tumor cells (p = 0.015 and p = 0.010, respectively). In the group of patients with isolated overexpression of pSTAT3, the 5-year OS and PFS were lower, and the risk of death and disease progression was almost 1.5 times higher than in patients with low protein expression (p = 0.015 and p = 0.011, respectively). When studying the co-expression of pSTAT3 and pSyk, the lowest OS and PFS were recorded in the subjects with a simultaneous high expression of these proteins. With this combination of markers, the probability of an adverse event in patients when calculating OS increased by 2.9 times (p = 0.003; hazard ratio 2.9; 95 % confidence interval 1.43–5.85), and when analyzing PFS – by 2.3 times (p = 0.021; hazard ratio 2.3; 95 % confidence interval 1.14–4.87) compared with other variants of their simultaneous expression.Conclusion. Overexpression of pSTAT3 is associated with unfavorable biological tumor characteristics and poor patient survival. The combined suprathreshold expression of the pSTAT3 and pSyk proteins is associated with lower OS and PFS values compared to their isolated expression.